Digital Interest in Nature-Based Accommodation: A Google Search Study of Glamping Popularity in Indonesia - Koswara, Asep; Kurniawati, Neni (Journal of Hospitality Accommodation Management (JHAM), 2025)
This study investigated digital interest in nature-based accommodation, particularly glamping, by analyzing Google Search data in Indonesia from 2019 to 2025. Glamping, a fusion of “glamorous” and “camping,” has emerged as a growing trend among urban travelers seeking comfort in natural environments. Using a descriptive observational approach, the research utilized Google Trends to assess search volume dynamics, popular queries, regional patterns, and seasonal spikes. The results revealed a steady increase in glamping-related searches, with notable peaks during holidays and weekends, indicating a strong connection between digital interest and domestic travel behavior. Popular destinations such as Bogor, Bandung, and Ciwidey dominated the search queries, while new keywords like “Bobocabin” and “Heha Ocean Glamping” indicated rising consumer preferences. Regional data showed that areas like Bali and Jakarta contributed most to glamping-related search activity. The findings highlight the value of Google Trends as a real-time tool for understanding tourism demand and consumer intent. This research provides valuable insights for tourism stakeholders to anticipate market shifts, optimize promotional strategies, and develop nature-based tourism offerings.